Performance of activities of daily living among hospitalized cancer patients. (March 2014) - Lindahl-Jacobsen, Line; Hansen, Dorte Gilså; Wæhrens, Eva Ejlersen; la Cour, Karen; Søndergaard, Jens
Abstract Background: Many cancer patients report unmet rehabilitation needs. Rehabilitation may include activities of daily living (ADL) tasks, but little is known about how cancer patients perform these tasks and how they prioritize their daily activities. Hence, this study aims to identify and characterize ADL task performance problems among a group of adult disabled hospitalized cancer patients using interview and questionnaire data. Methods: Cross-sectional study on prevalence of ADL task performance problems experienced by disabled hospitalized cancer patients using the Activities of Daily Living Questionnaire (ADL-Q) (n = 118) and the Canadian Occupational Performance Measure (COPM) (n = 55). Results: All 118 patients reported problems with ADL task performance. Based on the ADL-Q patients reported more problems within instrumental (I-)ADL than personal (P-)ADL. In both I-ADL and P-ADL the results differed between women and men. There was significant overlap between problems identified using the COPM and the ADL-Q instruments. Results from the COPM showed that 65% of problems were related to self-care, 25% to leisure, and 19% to productivity. Using both instruments identified more ADL problems than when using only one of the instruments. Conclusion: Adult hospitalized disabled cancer patients experience a high degree and variation in difficulties performing ADL, illustrating the need for a comprehensively planned assessment of problems and needs.